Activity-dependent sensory signal processing in mechanically responsive slowly conducting meningeal afferents - Übner, Michael; Carr, Richard W.; Meßlinger, Karl; De Col, Roberto (Journal of Neurophysiology, 2014)
Activity-dependent processes in slowly conducting afferents have been shown to modulate conduction and receptive properties, but it is not known how the frequency of action potential firing determines the responses of such fibers to mechanical stimulation. We examined the responses of slowly conducting meningeal afferents to mechanical stimuli and the influence of preceding action potential activity. In hemisected rat heads with adhering cranial dura mater, recordings were made from meningeal nerves. Dural receptive fields of mechanically sensitive afferent fibers were stimulated with a custom-made electromechanostimulator. Sinusoidal mechanical stimuli of different stimulus durations and amplitudes were applied to produce either high-frequency (phasic) or low-frequency (tonic) discharges. Most fibers showed slowing of their axonal conduction velocity on electrically evoked activity at >=2 Hz. In this state, the peak firing frequency of phasic responses to a 250-ms mechanical stimulus was significantly reduced compared with control. In contrast, the frequency of tonic responses induced by mechanical stimuli of >500 ms did not change. In a rare subtype of afferents, which showed conduction velocity speeding during activity, an increase in the phasic responses to mechanical stimuli was observed. Depending on the axonal properties of the afferent fibers, encoding of phasic components of mechanical stimuli is altered according to the immediate firing history. Preceding activity in mechanoreceptors slowing their conduction velocity seems to provide a form of low-pass filtering of action potential discharges predominantly reducing the phasic component. This may improve discrimination between harmless and potentially harmful mechanical stimuli in normal tissue.
EVALuna2:2457